2022
DOI: 10.1002/cam4.5017
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic importance of the preoperative New‐Naples prognostic score for patients with gastric cancer

Abstract: Background The wide applicability of the Naples prognostic score (NPS) is still worthy of further study in gastric cancer (GC). This study aimed to construct a New‐NPS based on the differences in immunity and nutrition in patients with upper and lower gastrointestinal tumors to help obtain an individualized prediction of prognosis. Methods This study retrospectively analyzed patients who underwent radical gastrectomy from April 2014 to September 2016. The cutoff values of the preoperative neutrophil‐to‐lymphoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 58 publications
1
4
0
Order By: Relevance
“… 23 , 24 Notably, NPS has been found to possess a better prognostic value compared to other markers in esophageal cancer and gastric cancer. 12 , 13 In our study, the ROC curves demonstrated that NPS exhibited a higher prognostic value in both the training group and the validation group.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“… 23 , 24 Notably, NPS has been found to possess a better prognostic value compared to other markers in esophageal cancer and gastric cancer. 12 , 13 In our study, the ROC curves demonstrated that NPS exhibited a higher prognostic value in both the training group and the validation group.…”
Section: Discussionsupporting
confidence: 53%
“…It was initially confirmed as an independent risk factor in colon cancers and further demonstrated its correlation with prognosis in esophageal cancer, pancreatic cancer, gastric cancer, and other types of cancers. [11][12][13][14] However, the predictive significance of NPS in patients with CCA has not yet been confirmed.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, future studies should reconstruct the New-NPS according to the nutritional status of patients with gastric cancer. Wang et al evaluated the new-NPS as a prognostic factor in patients with gastric cancer (25). In that study, the cutoff values used were 2.37 for NLR, 3.10 for LMR, 4.25 for albumin, and 156.81 for total cholesterol.…”
Section: Discussionmentioning
confidence: 99%
“…To determine the NPS score, all of these scores are added together. 6 In the study, patients were categorized into two groups based on their NPS score: those with a score of 0.1 to 2, and those with a score of 3 to 4. Major cardiovascular event (MACE) was defined as 1-year all-cause mortality, 1-year stroke, nonfatal recurrent MI, stroke, and MACEs were compared between the groups.…”
Section: Methodsmentioning
confidence: 99%
“…It has previously been used as a valuable prognostic tool in cancer patients. 6 NPS provides nutritional status and inflammation information. The long-term prognostic value of NPS has been previously demonstrated in a study of ST-segment elevation myocardial infarction (STEMI) patients.…”
Section: Introductionmentioning
confidence: 99%